2019
DOI: 10.1002/cphc.201900591
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Density Comparison of Noble Gas Hydrates Encapsulating Xenon, Krypton and Argon

Abstract: Understanding the effect of guest species on the host framework is important for the development of structure‐based properties of inclusion compounds. Herein, the crystal structures of the noble gas hydrates encapsulating Xe, Kr, and Ar were studied by powder X‐ray diffraction measurements. The crystal structures and hydration numbers of these noble gas hydrates were solved by Rietveld refinements using optimized models with the direct‐space technique. It was revealed that host cage size of these hydrates chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…Based on the obtained crystallographic structure of sI C 2 H 4 hydrate at 93 K, the volumes of its 5 12 and 5 12 6 2 cages at 93 K are 165 and 232 Å 3 , respectively, while the volumes of the 5 12 and 5 12 Earlier studies have shown that the 5 12 cages of Xe hydrate (174 Å 3 ) are larger than those of CH 4 hydrate (164 Å 3 ), while the 5 12 6 2 cages of Xe hydrate (226 Å 3 ) are smaller than those of CH 4 hydrate (230 Å 3 ). 32,33 The 5 12 cage of C 2 H 4 hydrate is smaller than that of Xe hydrate, although C 2 H 4 is larger than Xe and the unit cell of C 2 H 4 hydrate is larger than that of Xe hydrate (see Figure 1). Considering these facts, we conclude that the occupancy of the 5 12 cages of C 2 H 4 hydrate, which exceeds that of the 5 12 cages of C 2 H 6 hydrate, accounts for its greater size.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Based on the obtained crystallographic structure of sI C 2 H 4 hydrate at 93 K, the volumes of its 5 12 and 5 12 6 2 cages at 93 K are 165 and 232 Å 3 , respectively, while the volumes of the 5 12 and 5 12 Earlier studies have shown that the 5 12 cages of Xe hydrate (174 Å 3 ) are larger than those of CH 4 hydrate (164 Å 3 ), while the 5 12 6 2 cages of Xe hydrate (226 Å 3 ) are smaller than those of CH 4 hydrate (230 Å 3 ). 32,33 The 5 12 cage of C 2 H 4 hydrate is smaller than that of Xe hydrate, although C 2 H 4 is larger than Xe and the unit cell of C 2 H 4 hydrate is larger than that of Xe hydrate (see Figure 1). Considering these facts, we conclude that the occupancy of the 5 12 cages of C 2 H 4 hydrate, which exceeds that of the 5 12 cages of C 2 H 6 hydrate, accounts for its greater size.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The PXRD measurements were performed using an X-ray diffractometer (40 kV, 40 mA; Rigaku model Ultima-III) with parallel-beam optics and a low-temperature chamber. Finely powdered hydrate samples were prepared at a temperature below 100 K using a mortar and were mounted on a PXRD sample holder made of 2.5 mm thick copper (Cu) in the same approach used in our existing study . Each measurement was performed in a θ/2θ step scan mode with a step width of 0.02° using Cu Kα radiation (λ = 1.541 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Finely powdered hydrate samples were prepared at a temperature below 100 K using a mortar and were mounted on a PXRD sample holder made of 2.5 mm thick copper (Cu) in the same approach used in our existing study. 18 Each measurement was performed in a θ/2θ step scan mode with a step width of 0.02°u sing Cu Kα radiation (λ = 1.541 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Noble gas hydrates, and specifically helium clathrates, are perhaps one of the systems with less information available. [24][25][26][27][28][29][30][31][32][33][34][35] Although helium atoms and water molecules are the most frequent mono-and triatomic entities, respectively, in the universe, their interactions are weak and therefore, compounds are difficult to form. Nevertheless, it was possible to obtain the first helium clathrate hydrate in 2018 by filling ice XVI with helium atoms.…”
mentioning
confidence: 99%